First record of the Rosy goatfish, Parupeneus rubescens (Lacepede, 1801) (Mullidae) in Syrian marine waters - Sabour, Waad; Masri, Mai (Iraqi Journal of Aquaculture, 2023)
This paper discusses the first documented record of the Rosy goatfish Parupeneus rubescens in Syrian coastal waters. A specimen (200 mm TL) was captured on 21st May 2020, using trammel nets at a depth of 120 m. in the Ras al-Basit region, 60 km north of Lattakia (35°50′ N, 35°50′E). Morphological and taxonomic analysis showed that the type of individual described in the present work is a newly introduced species of Indo-Pacific origin to the area, identified as P. rubescens (Lacepede, 1801). It should be noted that this species was monitored with individuals of the species Parupeneus forsskali in the framework of our research project on the biology of the Mullidae family in the Syrian marine waters. The number of Lessepsian fish migrants in the Syrian marine waters has reached 82 species.